Creole fruits importance and characterization in two communities of Tuxpan, Veracruz - Lema F., Paulina; Pérez O., Ma. Antonia; Martínez D., María Teresa; Navarro G., Hermilio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Home-gardens or “Solares” in the communities Congregación (C) and Ejido (E) Juana Moza of Tuxpan, Veracruz are characterized by their high plant diversity. Fruit trees are an important component of this diversity. These fruits are used for food and income, among others. However, their physical and organoleptic characteristics are scarcely documented. This research aimed to characterize and evaluate the economic and nutritional importance of five species of creole fruits: Green and purple caimito (Chrysophyllum cainito L.), chalahuite (Inga paterno Harms), guaya (Melicoccus bijugatus Jacq.), zapote domingo (Mammea americana L.) and jobo (Spondias mombin L.). A sample of 63 heads of household was selected (24 in Ejido and 39 in Congregation Juana Moza), to whom a survey was applied. In addition, 30 lots (20 in C and 10 E) were sampled at harvest time, where 10 fruits from different parts of the trees were collected to evaluate the fruit diameter and length, and 3 fruits were taken per plot and species to determine the color, firmness, degrees Brix and acidity in a laboratory. The results indicated that caimito, Chalahuite and guaya are used as fresh fruit; zapote domingo and jobo are used to prepare refreshing drinks and liqueurs. In addition, jobo is used to prepare “curados” (a local alcoholic drink) and Chalahuite seeds are cooked and used as food. The characterization of the fruits indicated that variables such as weight, length and diameter were similar in both communities, while the degrees Brix and acidity had statistically significant differences. Local management and use of the fruits are important because families obtain fruit for self-consumption and income from April-September; in addition, the trees are used for shade, fencing, fire wood.